1990
DOI: 10.1002/j.1460-2075.1990.tb08082.x
|View full text |Cite
|
Sign up to set email alerts
|

The mannose 6-phosphate receptor cytoplasmic domain is not sufficient to alter the cellular distribution of a chimeric EGF receptor.

Abstract: Unlike most receptors, 300 kd mannose 6‐phosphate receptors (MPRs) are localized primarily in the trans‐Golgi network (TGN) and endosomes, and they cycle constitutively between these compartments. Yet, when present at the cell surface, MPRs are internalized together with other cell surface receptors in clathrin‐coated vesicles. We constructed a chimeric receptor, comprised of human EGF receptor extracellular and transmembrane domains joined to the bovine MPR cytoplasmic domain, to test whether the MPR cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The results of previous studies using chimeric proteins of EGFR-CIMPR or lysozyme-CIMPR have suggest that the cytoplasmic domain of CIMPR is not sufficient to mimic the CIMPR localization [21,22]. On the other hand, Mauxion et al [54], using a chimeric protein consisting of the ectodomain of the hemagglutinin of the influenza virus and CIMPR, showed that the cytoplasmic domain of CIMPR is sufficient to determine the steady-state distribution of CIMPR.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The results of previous studies using chimeric proteins of EGFR-CIMPR or lysozyme-CIMPR have suggest that the cytoplasmic domain of CIMPR is not sufficient to mimic the CIMPR localization [21,22]. On the other hand, Mauxion et al [54], using a chimeric protein consisting of the ectodomain of the hemagglutinin of the influenza virus and CIMPR, showed that the cytoplasmic domain of CIMPR is sufficient to determine the steady-state distribution of CIMPR.…”
Section: Discussionmentioning
confidence: 95%
“…The receptor cytoplasmic domain also contains other determinants for binding to the hVPS35 subunit of the retromer and tail-interacting protein of 47 kDa (TIP47), both of which, together with AP-1 and PACS-1, are involved in the recycling of the receptor from the endocytic compartments back to the TGN [18][19][20]. On the other hand, several earlier studies have proposed that the luminal domain, consisting of 15 repeated units, the amino acid sequences of which are similar to each other, is important in this recycling process [21][22][23]. The addition of the cytoplasmic tail of CIMPR to the luminal domain of the epidermal growth factor receptor (EGFR) or a secretory protein, lysozyme, failed to produce the typical localization pattern of CIMPR [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the CD8-reporter protein system avoids two potential pitfalls of using the full-length CIMPR for these studies. Firstly, the influence that the very large lumenal domain has on trafficking (Dintzis and Pfeffer, 1990;Dintzis et al, 1994;Conibear and Pearse, 1994) will be negated by using CD8 reporters as the lumenal domain of CD8 is small (~20 kDa) and has no known targeting information. Secondly, as the CD8 transmembrane domain was present in all of the reporter constructs, any effects of the CIMPR transmembrane domain upon its localisation were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…An influence of the extracytoplasmic domain of the M6P/IGF-II receptor on its trafficking was already noted earlier, e.g. a fusion protein, in which the extracytoplasmic domain of the M6P/IGF-II receptor was replaced by that of the epidermal growth factor receptor, was unable to be transported from the cell surface to the TGN (51).…”
Section: Discussionmentioning
confidence: 98%